Industrial manufacturing method of thin-gauge, high-strength, low-yield-ratio and H2S-corrosion-resistant hot-rolled plate coil

By adding trace Nb, Cr and other alloying to low-carbon C-Mn steel, combined with ultra-low sulfur smelting and TMCP controlled rolling and cold-controlled processes, the problem of difficult to produce low yield-strength and high-strength acid-resistant service steel products in the existing technology in the environment containing hydrogen sulfide is solved, and hot-rolled coil preparation with high strength, low yield-strength and hydrogen-cracking resistance is achieved, which is suitable for oil and gas conveying pipelines in acidic environments.

CN119506694APending Publication Date: 2025-02-25BAOTOU IRON & STEEL (GROUP) CO LTD

Patent Information

Application Number
CN202411475751.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to produce acid-resistant service steel products with low yield strength ratio and high strength in hydrogen sulfide-containing environments, especially in small diameter welded pipes formed by straight seam welding.

Method used

The main use of low-carbon C-Mn steel, adding trace Nb, Cr and other alloying, combined with ultra-low sulfur smelting control technology and TMCP controlled rolling and cooling technology, hot-rolled coils with excellent strength and toughness and anti-hydrocracking properties were prepared through KR molten desulfurization pretreatment, converter top-bottom blowing, LF refining, RH refining, slab continuous casting, reheating, rough rolling and finishing mill control rolling, cooling and coiling, etc.

Benefits of technology

It has achieved the production of hot-rolled coils with yield strength of 450MPa-565MPa, tensile strength of 535MPa-620MPa, and yield strength ratio of ≤0.88. It has the dual characteristics of resistance to hydrogen cracking and anti-hydrogen sulfide stress cracking, and is suitable for the construction of oil and gas conveying pipelines in acid service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506694A_ABST
    Figure CN119506694A_ABST
Patent Text Reader

Abstract

The invention discloses an industrial manufacturing method of a thin-gauge high-strength low-yield-ratio H2S-corrosion-resistant hot-rolled plate coil and discloses a specific production process flow, and the hot-rolled plate coil comprises the following chemical components in percentage by mass: 0.035%-0.055% of C, 0.10%-0.20% of S i, 1.00%-1.20% of Mn, less than or equal to 0.015% of P, less than or equal to 0.0015% of S, 0.03%-0.05% of Nb, less than or equal to 0.30% of Cr + T i, 0.02%-0.06% of Al and the balance of Fe and inevitable impurities. According to the component design, low-carbon C-Mn steel is used as a main component, trace Nb, Cr and the like are added for alloying, and the steel for the ERW welding pipe with low yield ratio and welding pipe forming performance, hydrogen induced cracking resistance and hydrogen sulfide stress cracking resistance is obtained by combining an ultra-low sulfur smelting control technology and a TMCP controlled rolling and controlled cooling technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical application field of steel products in acidic service environments, and in particular relates to an industrial manufacturing method for a thin-gauge high-strength, low-yield ratio, H2S corrosion-resistant hot-rolled coil. Background Art

[0002] Anti-H 2 S corrosion pipeline steel is mainly used for H-rich 2 S / CO 2 etc. + The transportation of acidic media such as crude oil, refined oil, natural gas, water, and coal gas. When metals are exposed to hydrogen sulfide, the H atoms produced in the electrochemical reaction process continuously penetrate and accumulate into the defect positions and stress concentration areas in the steel, which will cause corrosion and cracking of the steel even at a relatively low transportation pressure, which is extremely harmful. At present, the oil pipelines serving in hydrogen sulfide environments at home and abroad are mainly small-diameter welded pipes formed by straight seam welding such as ERW. The material has very strict requirements on the processing ability to resist deformation and rolling, especially a low yield strength ratio (≤0.88 or even ≤0.85). Since the straight seam welded pipe is limited by the transverse sampling angle, the influence of grain orientation on the yield strength ratio makes the production of thin-walled high-strength straight seam welded pipe parent material a great technical challenge.

[0003] 1. The alloy composition disclosed in Document 1 "A kind of acid corrosion resistant X65MS pipeline steel and its preparation method" (CN201810237038.9) is Mn+Nb+Ti+Cr+Ni+Cu, while the alloy composition of this patent is Mn+Nb+Cr+Ti, without adding Ni and Cu, the composition design is simple, and the alloy cost is lower; Document 2 S≤0.002%, while this patent adopts ultra-low sulfur control process to achieve S≤0.0015%, which is more advanced in control level.

[0004] 2. The alloy composition system disclosed in Document 2 "X65MS Acid-Resistant Pipeline Steel" (CN 111254352 B) is Mn+Nb+Ti+Cr+Ni, which is aimed at the production of thick-gauge products, with high total alloy content and high yield strength ratio. The alloy composition system of this patent is only Mn+Nb+Cr+Ti, without adding Ni, and the composition design is simple and economical. The product involved is suitable for the production of thin-gauge acid-resistant pipeline steel with low yield strength ratio requirements, which is progressive.

[0005] 3. The alloy composition system disclosed in Document 3 "A hot-rolled coil of X65MS pipeline steel resistant to acid corrosion and its preparation method" (202010243677.3) is Mn+Nb+V+Ti+Cr+Mo. The alloy composition system of this patent is only Mn+Nb+Cr+Ni+Ti, the composition design is simple, and the alloy cost is lower. No Ni, V, or Mo is added, and the control range of the precious metal Nb is only 0.03%-0.05%, which is different from Document 3 (0.05%-0.08%). Summary of the invention

[0006] The purpose of the present invention is to provide an industrial manufacturing method for thin-gauge high-strength, low-yield ratio, H2S corrosion-resistant hot-rolled coils, with a thickness range of ≤12 mm, a composition design based on low-carbon C-Mn steel, and the addition of trace amounts of Nb, Cr and the like for alloying, combined with ultra-low sulfur smelting control technology and TMCP controlled rolling and controlled cooling process, to obtain steel for acidic service pipelines with excellent strength and toughness, resistance to hydrogen-induced cracking and resistance to hydrogen sulfide stress cracking.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The invention discloses an industrial manufacturing method for a thin-gauge, high-strength, low-yield ratio, H2S corrosion-resistant hot-rolled coil, and the production process is as follows: KR hot metal desulfurization pretreatment - converter top and bottom blowing - LF refining - RH refining - slab continuous casting - reheating - roughing and finishing mill control rolling - cooling - coiling - pallet transportation system - sampling and inspection, wherein the roughing and finishing mill control rolling process includes roughing high-pressure water descaling - fixed-width press - E1 R1 roughing mill - E2R2 roughing mill - insulation cover - flying shear - finishing high-pressure water descaling - F1-F7 finishing mills; the invention is characterized in that:

[0009] Ultra-low sulfur smelting and continuous casting control process: ironmaking water needs to be treated by KR desulfurization, and the sulfur content of the molten iron entering the converter is required to be ≤0.002%, and the desulfurization slag cleaning area is greater than 95%; the tapping temperature is ≥1620℃ to ensure that the composition and temperature are coordinated for tapping; if there is a new tapping port or an abnormal turnover ladle, the tapping temperature shall be increased by 10℃-15℃ on the basis of the upper limit as appropriate; aluminum iron, silicon iron and manganese iron are added during the converter tapping process for deoxidation and alloying; LF furnace slag desulfurization, and aluminum iron, silicon iron, manganese iron and niobium iron alloy are added to adjust to the target composition range; the vacuum degree of the RH process is required to be ≤2.6mbar, and the vacuum time is maintained for ≥10min to ensure that the circulating pure degassing time is ≥7min; temperature measurement and sampling are carried out during the RH vacuum treatment; calcium treatment is carried out after the RH vacuum treatment is completed, and the soft blowing time is ensured to be greater than 10min after wire feeding to prevent the exposure of molten steel; the continuous casting billet light pressure technology is used to control the center segregation;

[0010] Slab heating and rolling process: The continuous casting slab thickness is 230mm, and the continuous casting slab is heated to

[0011] The target temperature is 1190℃, followed by two-stage controlled rolling through ≤8 rough rolling and 7 finishing rolling mills, with the intermediate billet ≤55mm and the finishing temperature ≤850℃. The steel is then cooled quickly and evenly by using the dense laminar cooling method and coiled at ≤560℃.

[0012] The chemical composition of the hot-rolled coil, in percentage by mass, is C: 0.035%-0.055%, Si: 0.10%-0.20%, Mn 1.00%-1.20%, P≤0.015%, S≤0.0015%, Nb: 0.03%-0.05%, Cr+T i≤0.30%, Al: 0.02%-0.06%, and the remainder is Fe and unavoidable impurities.

[0013] Furthermore, the chemical composition of the hot-rolled coil by mass percentage is C: 0.05%, Si: 0.12%, Mn: 1.15%, P: 0.010%, S: 0.001%, Nb: 0.042%, Cr+T i: 0.18%, Al: 0.024%, and the remainder is Fe and unavoidable impurities.

[0014] Furthermore, the chemical composition of the hot-rolled coil by mass percentage is C: 0.04%, Si: 0.13%, Mn: 1.13%, P: 0.012%, S: 0.001%, Nb: 0.046%, Cr+T i: 0.21%, Al: 0.029%, and the remainder is Fe and unavoidable impurities.

[0015] Furthermore, the chemical composition of the hot-rolled coil by mass percentage is C: 0.04%, Si: 0.15%, Mn: 1.14%, P: 0.011%, S: 0.001%, Nb: 0.044%, Cr+T i: 0.21%, Al: 0.031%, and the remainder is Fe and unavoidable impurities.

[0016] Furthermore, the performance of the hot-rolled coil meets the following technical requirements: yield strength 450MPa-565MPa, tensile strength 535MPa-620MPa, elongation ≥38%, yield strength ratio ≤0.88, -15℃ Charpy impact energy Akv ≥250J, -15℃ drop hammer tear shear section rate ≥90%, grain size >11 levels, crack sensitivity rate of hydrogen-induced cracking detection 0%, crack length rate = 0%, crack thickness rate = 0%, and no crack defects in the sulfide stress cracking four-point bending test.

[0017] Furthermore, it is used to manufacture X60MS / X65MS welded pipes that meet API 5L and GB / T 9711 sour service environments.

[0018] Furthermore, the hot-rolled coil has a special characteristic of a low yield ratio of ≤0.85 after being welded into pipes, and can be used not only in the manufacture of straight seam small-diameter welded pipes, but also in the construction of oil and gas pipelines serving in acidic environments.

[0019] Compared with the prior art, the beneficial technical effects of the present invention are:

[0020] (1) The design is based on low-carbon and low-manganese steel, without adding Mo elements. The content of precious metals Cr, Ni, and Ti elements is flexibly matched according to user needs. It not only effectively compensates for the strength loss caused by low C and low Mn, but also helps enterprises reduce costs and increase efficiency. At the same time, it reduces the risk of corner cracks in the casting, and has design flexibility and significant progress.

[0021] (2) The product combines ultra-low sulfur smelting continuous casting and thermomechanical controlled rolling processes, and has the dual characteristics of resistance to hydrogen-induced cracking (HIC) and sulfide stress cracking (SSC). The product performance indicators meet the requirements of YB / T 4841 standard and can be used to manufacture X60MS / X65MS welded pipes in sour service environments that meet API 5L and GB / T 9711. After welding and pipe making, the material has the special characteristic of a low yield ratio of ≤0.85, which can not only be used in the manufacture of straight seam small-diameter welded pipes, but also the welded steel pipes can be used in the construction of oil and gas pipelines in sour service environments, with good social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described below in conjunction with the accompanying drawings.

[0023] Figure 1 The metallographic structure of the hot-rolled coil obtained in the embodiment of the present invention. DETAILED DESCRIPTION

[0024] The embodiments are only descriptions of the preferred modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

[0025] The main elements were chosen for the following reasons:

[0026] C: The C content in steel is an element that is easy to segregate. It will aggravate the segregation of carbides in the center of the ingot. After rolling, it is easy to form pearlite banded structure, which will seriously affect the sensitivity of steel to hydrogen-induced cracking. Therefore, the design idea of ​​using low-carbon components is to remove the precious metals Mo and Cu so that the product still has a certain resistance to hydrogen. 2 Based on the design basis of S corrosion resistance, the present invention controls the carbon content to ≤ 0.055%.

[0027] Mn: Manganese can be infinitely substituted with iron for solid solution, and is a good solid solution strengthening element. However, in terms of hydrogen sulfide resistance, manganese, like carbon and phosphorus, is easily enriched in the center of the ingot to form a hard phase segregation zone, and after rolling, pearlite banded structure is generated, resulting in a decrease in the HIC performance of the steel. Therefore, the manganese content of the present invention is ≤1.20%.

[0028] P: The component segregation band in steel is one of the important factors affecting the sensitivity to hydrogen-induced cracking, and the P element is very easy to segregate during the crystallization process in steel, resulting in uneven composition and structure, and increasing the sensitivity to hydrogen-induced cracking. Therefore, the present invention controls the P content to P≤0.015%.

[0029] S: is an extremely harmful element in acidic service pipeline steel, which sharply increases the sensitivity of HIC and SSC. The MnS inclusion formed by S and Mn is the most likely nucleation site for HIC. Generally, MnS can be made into dispersed spheres through calcium treatment, thereby inhibiting the formation of HIC and significantly reducing the crack sensitivity. Therefore, the present invention controls the S content to S≤0.0015% through ultra-low sulfur controlled smelting technology.

[0030] Nb: Niobium has the function of improving the strength and toughness of steel, and has become the most typical and widely used microalloying element. Niobium carbonitride can precipitate from austenite during heating and rolling, or precipitate at the phase boundary during phase transformation, or precipitate from supersaturated ferrite during the final cooling process to refine the grains. Nb is the main element for grain refinement strengthening, but iron alloys are expensive, so the present invention controls the niobium content to ≤0.05%.

[0031] Cr: Chromium is important for slowing down CO 2 -H 2 The corrosion rate in SC l- environment is extremely favorable; on the other hand, its dispersed carbides are also strong traps for hydrogen, so the Cr content should be sufficient if conditions permit, and Cr can improve hardenability, so that the steel has better comprehensive mechanical properties after quenching. Generally, the Cr content is controlled at ≤0.28%.

[0032] Ti: TiC and TiN tend to gather in the thickness center during the solidification process of the steel billet to form micro-inclusions with sharp edges, which can easily lead to hydrogen-induced cracking. However, an appropriate amount of trace Ti elements can reduce the probability of corner cracks in the billet, so the content should not be too high and is generally controlled at ≤0.015%.

[0033] Example

[0034] The present invention will be further described below by way of examples.

[0035] The weight percentages of the components used in the experimental steels of Examples 1 to 3 are shown in Table 1, Table 2 shows the specific process system of each example, Table 3 shows the mechanical properties of the steels of each example, Table 4 shows the hydrogen-induced cracking and hydrogen sulfide stress cracking properties of the parent materials of the examples (Note: there is no hydrogen blistering on the surface of the samples). Table 5 shows the tensile properties after welding and pipe making.

[0036] in Figure 1 The metallographic structure of the embodiment is shown, and it can be seen that the metallographic structure is ferrite + granular bainite, the grains are fine and uniform, there is no banded structure, and the grain size is about 11 levels.

[0037] Table 1: Chemical composition of steel in various examples (wt, %)

[0038] Example C Si Mn P S Al Nb Cr+Ti 1 0.05 0.12 1.15 0.010 0.001 0.024 0.042 0.18 2 0.04 0.13 1.13 0.012 0.001 0.029 0.046 0.21 3 0.04 0.15 1.14 0.011 0.001 0.031 0.044 0.21

[0039] Table 2: Process system of each embodiment

[0040]

[0041]

[0042] Table 3: Mechanical properties of steel in various examples

[0043]

[0044] Table 4 Hydrogen induced cracking and hydrogen sulfide stress cracking properties of the parent material of the embodiment

[0045]

[0046] Table 5: Tensile properties of steel pipes after welding in various examples

[0047]

[0048] It can be seen from the embodiment combined with Table 3 and Table 4 that the steel of the embodiment of the present invention has excellent performance and sufficient surplus, yield strength of 470MPa-505MPa, tensile strength of 535MPa-650MPa, elongation ≥38%, yield strength ratio ≤0.88, -15℃ Charpy impact energy A kv ≥250J, -15℃ drop hammer tear shear section rate ≥92%, grain size>11, crack sensitivity rate (CSR) of hydrogen induced cracking (HIC) test = 0%, crack length rate (CLR) = 0%, crack thickness rate (CTR) = 0%, sulfide stress cracking (SSC) four-point bending test has no crack defects, and all product indicators meet the requirements of X60MS / X65MS specifications in YB / T 4841. After welding, the pipe is affected by the Bauschinger effect, the strength is reduced, and the yield strength ratio is ≤0.85.

[0049] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. An industrial manufacturing method for a thin-gauge, high-strength, low-yield ratio, H2S corrosion-resistant hot-rolled coil, the production process of which is: KR hot metal desulfurization pretreatment - converter top and bottom blowing - LF refining - RH refining - slab continuous casting - reheating - roughing and finishing mill control rolling - cooling - coiling - pallet transportation system - sampling and inspection, wherein the roughing and finishing mill control rolling process includes roughing high-pressure water descaling - fixed-width press - E1 R1 roughing mill - E2R2 roughing mill - insulation cover - flying shear - finishing high-pressure water descaling - F1-F7 finishing mill; characterized in that: Ultra-low sulfur smelting and continuous casting control process: ironmaking water needs to be treated by KR desulfurization, and the sulfur content of the molten iron entering the converter is required to be ≤0.002%, and the desulfurization slag cleaning area is greater than 95%; the tapping temperature is ≥1620℃ to ensure that the composition and temperature are coordinated for tapping; if there is a new tapping port or an abnormal turnover ladle, the tapping temperature shall be increased by 10℃-15℃ on the basis of the upper limit as appropriate; aluminum iron, silicon iron and manganese iron are added during the converter tapping process for deoxidation and alloying; LF furnace slag desulfurization, and aluminum iron, silicon iron, manganese iron and niobium iron alloy are added to adjust to the target composition range; the vacuum degree of the RH process is required to be ≤2.6mbar, and the vacuum time is maintained for ≥10min to ensure that the circulating pure degassing time is ≥7min; temperature measurement and sampling are carried out during the RH vacuum treatment; calcium treatment is carried out after the RH vacuum treatment is completed, and the soft blowing time is ensured to be greater than 10min after wire feeding to prevent the exposure of molten steel; the continuous casting billet light pressure technology is used to control the center segregation; Slab heating and rolling process: The continuous casting slab thickness is 230mm. The continuous casting slab is heated to the target temperature of 1190℃ by a walking beam heating furnace and then subjected to two-stage controlled rolling by a rough rolling unit of ≤8 passes and a finishing rolling unit of 7 passes. The intermediate slab is ≤55mm, and the finishing rolling temperature is ≤850℃. Then, the slab is cooled quickly and evenly by an intensified laminar cooling method, and coiled at a temperature of ≤560℃. The chemical composition of the hot-rolled coil, measured by mass percentage, is C: 0.035%-0.055%, Si: 0.10%-0.20%, Mn 1.00%-1.20%, P≤0.015%, S≤0.0015%, Nb: 0.03%-0.05%, Cr+Ti≤0.30%, Al: 0.02%-0.06%, and the remainder is Fe and unavoidable impurities.

2. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: The chemical composition of the hot-rolled coil by mass percentage is C: 0.05%, Si: 0.12%, Mn: 1.15%, P: 0.010%, S: 0.001%, Nb: 0.042%, Cr+Ti: 0.18%, Al: 0.024%, and the remainder is Fe and unavoidable impurities.

3. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: The chemical composition of the hot-rolled coil by mass percentage is C: 0.04%, Si: 0.13%, Mn: 1.13%, P: 0.012%, S: 0.001%, Nb: 0.046%, Cr+Ti: 0.21%, Al: 0.029%, and the remainder is Fe and unavoidable impurities.

4. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: The chemical composition of the hot-rolled coil, in percentage by mass, is C: 0.04%, Si: 0.15%, Mn: 1.14%, P: 0.011%, S: 0.001%, Nb: 0.044%, Cr+Ti: 0.21%, Al: 0.031%, and the remainder is Fe and unavoidable impurities.

5. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: The performance of the hot-rolled coil meets the following technical requirements: yield strength 450MPa-565MPa, tensile strength 535MPa-620MPa, elongation ≥38%, yield strength ratio ≤0.88, -15°C Charpy impact energy Akv ≥250J, -15°C drop hammer tear shear section rate ≥90%, grain size >11 levels, crack sensitivity rate of hydrogen-induced cracking detection 0%, crack length rate = 0%, crack thickness rate = 0%, and no crack defects in the sulfide stress cracking four-point bending test.

6. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: Used to manufacture X60MS / X65MS welded pipes that meet API 5L and GB / T 9711 sour service environments.

7. The industrial manufacturing method of thin-gauge high-strength low-yield ratio H2S corrosion resistant hot-rolled coil according to claim 1, characterized in that: The hot-rolled coil has a special characteristic of a low yield ratio of ≤0.85 after being welded into a pipe, and can not only be used in the manufacture of straight seam small-diameter welded pipes, but the welded steel pipes can also be suitable for the construction of oil and gas pipelines serving in an acidic environment.

Citation Information

Patent Citations

  • Chromium-molybdenum-free H2S-corrosion-resistant L360MS hot rolled steel strip for spiral welded pipe and manufacturing method of chromium-molybdenum-free H2S-corrosion-resistant L360MS hot rolled steel strip

    CN112522602A

  • Industrial manufacturing method of low-cost hot-rolled plate coil for hydrogen-doped gas pipeline with yield strength of 360 MPa

    CN116408349A

  • Industrial manufacturing method of economical thick-specification extremely-cold-resistant X60MS hot-rolled plate coil

    CN118497592A

  • Design and manufacturing method of thick-specification economical X52MS H2S corrosion resistant hot-rolled coiled plate

    CN118547207A

Cited By

  • Industrial manufacturing method of economical thick-specification steel hot-rolled plate coil for carbon dioxide pipeline transportation

    CN120443036A